(untitled) (International Journal of Environmental Sciences, 2025)
The purpose of this paper is to obtain a mystical story regarding the Dark Tourism Destination Japanese Cave in North Sulawesi. To collect the data related to mystical stories in the dark tourism sites of Japanese Cave in Manado City and Kawangkoan Minahasa, the researcher used a literature study research design. Researchers used literature studies by reading numbers of references in the form of books, articles, journals, newspaper, news through the youtube platform to find relevant information. One of interesting story comes from a haunted atmosphere in Kawangkoan Japanese Cave, since this place used to be a place of torture for residents. Local people said that tourists should not try to enter the cave alone because they will get lost, and the numbers of apparition were often seen. The cave is indeed one of the historical relics in Indonesia as a Japanese colony. The reason is, in the colonial era, the Japanese army used caves as their bunkers or fortifications. A mystical and haunted impression is often attached to Japanese caves, considering that the construction process uses a forced labor system. Moreover, at that time the caves were often used as a place to torture prisoners until they lost their lives. The Japanese Cave in Kiawa Kawangkoan Minahasa Village and the Japanese Cave in Manado City are dark tourist destinations in North Sulawesi that can be promoted through mystical stories that arise from stories and beliefs of the local community.